2019
DOI: 10.1080/21645515.2019.1593729
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel vaccines against human cytomegalovirus

Abstract: Congenital human cytomegalovirus (HCMV) infection and HCMV infection of the immunosuppressed patients cause significant morbidity and mortality, and vaccine development against HCMV is a major public health priority. Efforts to develop HCMV vaccines have been ongoing for 50 y, though no HCMV vaccine has been licensed; encouraging and promising results have obtained from both preclinical and clinical trials. HCMV infection induces a wide range of humoral and T cell-mediated immune responses, and both branches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 130 publications
(207 reference statements)
1
20
0
Order By: Relevance
“…Though the pentameric complex elicits a high titer of HCMV neutralization activity, the antibodies elicited are protective against HCMV infection of epithelial cells, endothelial cells and monocytes, but not fibroblasts or primary trophoblast progenitor cells [ 46 , 47 , 48 , 49 , 68 , 69 , 70 , 71 ]. It has been suggested that the combination of trimeric gB and pentameric complex proteins may be an optimal prophylactic HCMV vaccine [ 37 , 72 , 73 ]. The effect of gB in combination with pentameric complex has been evaluated using MVA vectored or RNA vaccine that simultaneously express gB and the pentameric complex [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the pentameric complex elicits a high titer of HCMV neutralization activity, the antibodies elicited are protective against HCMV infection of epithelial cells, endothelial cells and monocytes, but not fibroblasts or primary trophoblast progenitor cells [ 46 , 47 , 48 , 49 , 68 , 69 , 70 , 71 ]. It has been suggested that the combination of trimeric gB and pentameric complex proteins may be an optimal prophylactic HCMV vaccine [ 37 , 72 , 73 ]. The effect of gB in combination with pentameric complex has been evaluated using MVA vectored or RNA vaccine that simultaneously express gB and the pentameric complex [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of experimental vaccine approaches have been evaluated over the past 50 years. Although live attenuated, subunit, DNA/RNA and viral vectored HCMV vaccines have each demonstrated promising results, none of them meet the requirements of licensing [ 34 , 35 , 36 , 37 ]. An HCMV recombinant gB vaccine adjuvanted with MF59 has advanced the furthest in clinical trials [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies elicited by the pentameric complex are likely to prevent HCMV infecting epithelial cells, endothelial cells, and monocytes, but not fibroblasts or primary trophoblast progenitor cells [58,59,60,61,62,63,64,65]. Since HCMV gB elicits higher HCMV neutralization activity for fibroblasts than epithelial cells, whereas the pentameric complex mainly elicits high HCMV neutralization activity for epithelial cells, endothelial cells, and monocytes, it has been suggested that an optimal prophylactic HCMV vaccine will consist of both trimeric gB and pentameric complex proteins [31,66]. Immunization with the combination of gB and the pentameric complex has been tried using RNA vaccine or the MVA vectored vaccine expressing simultaneously gB and the five subunits of the pentameric complex, although enhanced HCMV-neutralizing activity was induced, no synergistic or additive effects in the elicitation of HCMV-neutralizing activity was reported [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no HCMV vaccine approved for clinical use, although the development of an HCMV vaccine is a public heath priority. Over the past 50 years, a variety of experimental vaccine approaches have been evaluated, and many are currently in various stages of evaluation [28,29,30,31]. An HCMV vaccine consisting of an adjuvanted recombinant monomeric gB protein has advanced the furthest in clinical trials [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Both vaccines were used to immunize mice and induce a neutralizing antibody response 10-fold higher compared to their soluble recombinant protein counterpart [90]. The vaccine was entered in phase I clinical studies enrolling HCMV-seronegative individuals for evaluation of safety and immunogenicity in early 2016 [91]. An additional eVLP vaccine candidate, targeting both the gB and pp65 antigens, has also been manufactured by VBI.…”
Section: Virus-like Particles and Nanoparticles For Antigen Displaymentioning
confidence: 99%